Visit of Prime Minister Dr. Manmohan Singh to Philippines, January 13-15, 2007. - Manmohan Singh 1932-; India. Ministry of External Affairs. Public Diplomacy Division (New Delhi Public Diplomacy Division, Ministry of External Affairs, Government of India, 2007)
Transcripts of the speech of Indian prime minister Manmohan Singh, chairman's statements on 5th ASEAN-India Summit and 2nd East Asia Summit, and Cebu Declaration on East Asian Energy Security.
Keywords: Manmohan Singh -- 1932- -- Travel -- Philippines; Visits of state -- Philippines; Summit meetings -- Philippines; India -- Foreign economic relations -- Southeast Asia; Southeast Asia -- Foreign economic relations -- India; India -- Foreign economic relations -- East Asia; East Asia -- Foreign economic relations -- India